Entrepreneurship Curricula and Instruction: Lesson learned from the United States - Nisa Novia Avien Christy; Suryaneta Suryaneta (Universitas Muhammadiyah Kalimantan Timur, 2022)
The higher rate of Indonesian unemployment than western countries has become an urgent issue that must be addressed immediately. One of the primary reasons is the entrepreneurial shortcomings of Indonesians. This study is conducted to synthetically analyze the empirical experiences of enhancing entrepreneurship in the United States as one of successful western countries. This further understanding will be transformed and applied to Indonesian universities and societies. This study uses literature analysis approaches to find references to relevant theory with the hope that researchers can in-depth understand the experiences and the significant factors facilitating entrepreneurship in the United States. At the end of the study, the authors conclude that entrepreneurship's success in the United States is due to central government support for entrepreneurship. Therefore, the success of entrepreneurship in the United States that can be applied in Indonesia, such as: (1) the Indonesian government must endeavor to oblige all universities in Indonesia to provide entrepreneurship classes, (2) promote entrepreneurship education and make entrepreneurship a priority, (3) implementing entrepreneurship in educational curricula at all levels, starting with preschool; (4) providing educational scholarship facilities for economic and business actors to become entrepreneurs, and (5) providing (people's business credit) with low interest for business.